2006
DOI: 10.1538/expanim.55.369
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Characteristics of Hatano High-and Low-Avoidance Rats

Abstract: Abstract:Hatano high-and low-avoidance (HAA and LAA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Therefore, further study of blood pressure is needed in older LAA rats, since age-related CPN was observed in all of the LAA rats. While polyarteritis nodosa also involves vasculitis associated with immune complex deposition that can lead to renal failure, the occurrence of polyarteritis nodosa might also be related to the fact that antibody production is higher in LAA rats than in HAA rats 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further study of blood pressure is needed in older LAA rats, since age-related CPN was observed in all of the LAA rats. While polyarteritis nodosa also involves vasculitis associated with immune complex deposition that can lead to renal failure, the occurrence of polyarteritis nodosa might also be related to the fact that antibody production is higher in LAA rats than in HAA rats 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Because there are close interconnections among nervous, endocrine, and immune systems, HAA and LAA lines may have differences in immunological activity. Therefore, the plasma levels of IgG, IgM, complement 3 (C3), classical pathway hemolytic complement (CH50), and beta-2-microglobulin were compared between males of the two lines at 5 and 24 weeks of age [28]. The plasma levels of IgG and CH50 were lower in the LAA line than in the HAA line at 5 weeks of age, whereas the differences disappeared at 24 weeks of age.…”
Section: Immunological Differences In Hatano Ratsmentioning
confidence: 99%
“…There were no differences between the two strains in the plasma levels of IgM, C3, and beta-2-microglobulin. Antibody production to sheep red blood cells (SRBC) and mitogen-induced lymphocyte proliferation were compared between 12-week-old males of the two lines [28]. Antibody responses in the PFC assay, plasma anti-SRBC-IgM levels, and spleen weights were higher in LAA lines than in HAA lines.…”
Section: Immunological Differences In Hatano Ratsmentioning
confidence: 99%
“…The animals were anesthetized with sodium pentobarbital, and blood was collected from the posterior vena cava, prior to sacrifice. The spleen was weighed, and the spleen cells were subjected to a plaque-formation cell (PFC) assay as previously described [26]. The blood's lymphocyte count was analyzed by an automated hematology analyzer (CellDyn3500, Abbott Laboratories), and then the serum was separated and stored at -80°C until determination of anti-SRBC-IgM [26].…”
Section: Immune Response To Sheep Red Blood Cells (Srbc)mentioning
confidence: 99%
“…Using these two strains, we have developed new methods for the risk assessment of the toxicological effects of substances on the behavior of the next-generation [28,30]. Although the Hatano rats are separated by their avoidance performance as mentioned above, characteristic differences between the strains are not only observed in their behaviors but also in their reproductive function [2,35,36,38], immunological reactions [26], and stress responses [1,3,31]. For example, compared to HAA rats, LAA rats show lower running-wheel activity, later sexual maturation, 5-day estrous cycling, lower sperm motility, more pronounced immunological reactions, and are generally less reactive to stress.…”
Section: Introductionmentioning
confidence: 99%